ANION RECOGNITION BY ACYCLIC REDOX-RESPONSIVE AMIDE-LINKED COBALTOCENIUM RECEPTORS - Beer, P; Hazlewood, C; Hesek, D; Hodacova, J; Stokes, S (1993)
New acyclic tripodal mono- and 1,1′-bis-substituted amide-linked cobaltocenium ligands have been prepared. Proton NMR spectroscopic and cyclic voltammetric anion co-ordination investigations reveal that the combination of a positively charged cobaltocenium unit together with an amide N-H group are the essential components for the molecular and electrochemical recognition of anionic guest species. Correlations were found to exist between Hammett σ p values of electron-donating and -withdrawing substituents of monosubstituted aryl amide cobaltocenium derivatives and relative magnitudes of halide-anion induced perturbations of the amide proton NMR chemical shift and cathodic shift of the respective cobaltocenium-cobaltocene reduction redox couple.